Effect of synthetic steroids on GABAA receptor binding in rat brain - Rey, Mariana (2015)
Neuroactive steroids (NAS), like allopregnanolone (A) and pregnanolone (P), bind to specifics sites on the GABAA receptor complex and modulate receptor function. They are capable to inhibit or stimulate the binding of GABAA receptor specific ligands, like t-butyl-bicyclophosphorothionate, flunitrazepam and muscimol. We have previously characterized a set of oxygen bridged synthetic steroids (SS) analogues to A or P using synaptosomes. Considering that the subunit composition of the GABAA receptor throughout the central nervous system affects the magnitude of the modulation of the GABAA receptor by NAS, here we evaluate the action of two selected SS, in brain sections containing cerebral cortex and hippocampus using quantitative receptor autoradiography. Both SS affected the binding of the three ligands in a similar way to A and P, with some differences on certain cerebral cortex layers according to the ligand used. One of the SS, the 3a-hydroxy-6,19-epoxypregn-4-ene-20-one (compound 5), behaved similarly to the natural NAS. However, significant differences with compound 5 were observed on hippocampus CA2 region, making it steroid suitable for a specific action. Those differences may be related to structural conformation of the SS and the subunits composition present on the receptor complex.